REPRESENTATION OF SOCIAL CRITICISM OF DISABILITY INFRASTRUCTURE IN INDONESIA IN THE VIDEO OF MALING (MAMAT KELILING) ON THE HAS CREATIVE YOUTUBE CHANNEL - Pratiwi, Feny; Astuti, Misni; Krisdiyanto, Irvan (Program Studi Ilmu Komunikasi Fakultas Ilmu Komunikasi Universitas Sumatera Selatan, 2024)
ABSTRACT Adityanta Dani Darmawan or more familiarly known as Dani Aditya is a comedian who started his career by participating in stand up comedy talent search events and also as a speaker for people with disabilities. Dani together with Mamat Alkatiri conveyed their opinions and social criticism regarding the infrastructure for people with disabilities in Indonesia which was packaged in comedy form on the Has Creative YouTube Channel. The aim of this research is to find out how Dani and Mamat convey social criticism. The method used in this research is a qualitative method using Charles Sanders Pierce's semiotic critical discourse model. The data collection technique used was direct observation, namely by watching Mamat Alkatiri and Dani's YouTube videos and by using library research, namely by using journals and books related to communication and social criticism. The results of this research show that Mamat Alkatiri and Dani explained many things and provided opinions and criticism regarding the infrastructure for people with disabilities in Indonesia, starting with paid concerts, it was very good to provide a special place for people with disabilities, but if it was a folk concert or an unpaid concert, Dani could not find facilities. This means that the infrastructure at stations and airports where seats are mostly used by non-disabled people and finally regarding education for disabled people, according to Dani and Mamat, it can be said that it is very far for disabled people to be able to participate because there are not yet adequate facilities and teachers who can providing learning for people with disabilities. Keywords: Social Criticism, Discourse Analysis, Representation ,Has Creative